PENGARUH PENEBANGAN TERKENDALI DAN KONVENSIONAL TERHADAP KERUSAKAN TEGAKAN TINGGAL DAN PRODUKTIVITAS KERJA - Sona Suhartana (Jurnal Penelitian Hasil Hutan, 2001)
The study was carried out at a forest company in West Kalimantan in 2000. The aim of the study is to know the effect of controlled and conventional felling to residual stand damage and work productivity.Data collected were: felled and damaged trees, trees with diameter of 20 cm and up, diameter and length of log, and felling time. The data was analyzed by t-test.The results of the study showed:I) The average of residual stand damaged is 7.05% for the controlled felling and 11.75% for conventional felling. This difference of 4.70% is significant.2) The average of work productivity were 17.462 m3/hr for the controlled felling and 24.094m3/hr for conventional felling. This difference of 6.632 m3/hr is highly significant. Key words: residual stand damages, felling productivity, controlled felling technique, conventional felling technique